A projeção especular de uma nova teoria da alma humana - Crestani, Jaison Luís (Universidade de São Paulo - Faculdade de Filosofia, Letras e Ciências Humanas, 2012)
In the tradition of Machadian studies, the short story O espelho tends to be analysed in a critical perspective that legitimizes the supposed seriousness of the arbitrary speech of the narrator-character Jacobina. From this point of view, the narrative is understood according to philosophical, existential and psychological standards, and the extravagant metaphysical theories of Jacobina are considered as a valid and authentic demonstration of the human essence. Trying to overcome these interpretative distortions, this paper proposes a redefinition of critical perspectives in order to give priority to the analysis of structural procedures that mobilize a strategic irony with the aim of disqualifying this narrator-character and satirizing the content of his metaphysical investigations.

Na tradição dos estudos machadianos, o conto O espelho tende a ser apreciado criticamente por uma perspectiva de leitura que legitima a suposta seriedade do discurso arbitrário do narrador-personagem Jacobina. Sob esse ângulo, o conto é entendido em chave filosófica, existencial e psicológica, e as extravagantes teorias metafísicas de Jacobina são consideradas como uma demonstração válida e autêntica da essência humana. Desse modo, na tentativa de contornar essas distorções interpretativas, este trabalho propõe uma redefinição das perspectivas de análise com o intuito de priorizar a apreciação dos procedimentos estruturais, que mobilizam uma ironia estratégica empenhada em desqualificar esse narrador e em satirizar o conteúdo de suas investigações metafísicas.
The mirror projection: a new theory of the human soul
Keywords: short stories; narrator; irony; satire; contos; narrador; ironia; sátira